Exploring Undergraduate Students’ Experience in Translation Activity in Poetry Class - Larasaty, Gina; Fakruddin , Afief (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
Learning poetry is not easy, especially when it comes to understanding poetry. In understanding a poem, students usually do translating activities to help them obtain information and the main message. This study aims to discover the students' experience and difficulties in poetry translation in the poetry classroom. The participants of this study were The Wiralodra University students who took Poetry Classes. The researcher used the qualitative method to analyze the data in this study. The results showed the students experience difficulty in poetry translation. The students' responses find poetry translation difficult and never do it apart in a poetry class. Some problems that students face in poetry translation such as: finding equivalent words, translating culture, maintaining poetic structure, understanding metaphorical expressions, and maintaining melodic elements. Then, holding the melody element dominated the student's difficulty in poetry translation, followed by maintaining poetic structure and understanding metaphorical experience. As the solution that they preferred predominated, they ignored the problems and continued to overcome their challenges in translating poetry with ease. The suggestion for further research is to explore the reasons for their preferred solution to overcome the problem in poetry translation.